Expressão gênica em trigo em resposta a infecção por puccinia triticina, agente casual da ferrugem da folha - Casassola, Alice (2015)
Wheat leaf rust is caused by the fungus Puccinia triticina and is one of the major diseases which annually affect the wheat crop in southern Brazil. The use of cultivars with durable genetic resistance has been essential to the progress of the culture. Thus, this study investigated which genes, mechanisms and metabolic pathways are involved in the durable adult plant resistance (APR) of wheat cv. Toropi. At the Brazilian Agricultural Research Corporation (Embrapa Trigo), wheat plants of the cv. Toropi were cultivated in growth chambers with controlled environment; inoculation of flag leaves with B55 race (MDT-MR) of P. triticina (MDT-MR) was performed; flag leaves were collected in different time-points postinoculation (0, 1, 3, 6, 12, 24, 48 and 72 hours after inoculation) and the RNA was extracted and purified. Analyses of gene expression by RT-qPCR were performed at the National Institute of Agricultural Botany (NIAB) in Cambridge/England, during the completion of doctorate sandwich. The sequencing of the post-inoculation timepoints was performed by The Genome Analysis Centre (TGAC), Norwich/England. Analyses of bioinformatics were conducted in two stages, in NIAB during the completion of sandwich doctorate, and after at the multi-user laboratory of Embrapa Informática Agropecuária CNPTIA and Embrapa Trigo. The expression analysis using gene primers related to the plant defense in wheat by RT-qPCR showed that classical defense mechanisms as lignification, oxidative stress, energy generation, lipids and water flow and cell cycle were altered during the process of infection and may be pathogen modulated in order to benefit its development. In sequencing and bioinformatics of the time-points 0, 6, 12 and 24 hai were obtained 463.371 contigs of which 19.633 were differentially expressed over time. The main metabolic pathways altered during the process of infection by leaf rust were generation of energy and metabolic precursors; catabolism; response to biotic and abiotic stresses; and transportation. Twelve of Toropi contigs were expressed only in the presence of the pathogen and not have homology in cv. Chinese Spring, may represent essential genes to the defense process. The understanding of this resistance enables their use in genetic improvement of wheat in order to obtain cultivars with durable genetic resistance